Peran Perbankan Syariah Terhadap Perusahaan Umum Milik Daerah Di Kota Cirebon - Wartono, Tono; Darmun, Darmun; Sari, Yekti Nila; Bahtiar, Bahtiar; Sari, Nindia Wulan (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2024)
Study purpose. This study aims to analyse the role of Islamic banking in supporting the development of Regional Owned Enterprises (BUMD) in Cirebon City. Materials and methods. A qualitative approach was used with a case study method, through in-depth interviews with managers and staff of Islamic banks and BUMD leaders. Results. The results of the study indicate that Islamic banking plays an important role in sharia-based financing, financial assistance, supervision of fund use, and improving sharia financial literacy. This collaboration has been proven to encourage operational efficiency and improve the institutional performance of BUMDs. However, challenges remain, such as limited sharia literacy and regulatory support. Conclusion. This study concludes that synergy between Islamic banking, BUMDs, and local governments is essential to optimise sustainable regional economic development in accordance with Islamic principles.